2022
DOI: 10.1155/2022/3163854
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Severity of COVID-19 Pandemic Amidst the Emerging SARS-CoV-2 Variants: Adoption of ARIMA Model

Abstract: Currently, the global report of COVID-19 cases is around 110 million, and more than 2.43 million related death cases as of February 18, 2021. Viruses continuously change through mutation; hence, different virus of SARS-CoV-2 has been reported globally. The United Kingdom (UK), South Africa, Brazil, and Nigeria are the countries from which these emerged variants have been notified and now spreading globally. Therefore, these countries have been selected as a research sample for the present study. The datasets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…5,6 In elaborating on the context, the WG asserted that reluctance was a behavioral phenomenon that was vaccine-specific and context-specific and is measured in the light of the available immunization services against an expectation of meeting a specific vaccine coverage goal. 7 Research conducted by Marti et al 8 indicated that while high hesitancy levels lead to lower demand for vaccines, low hesitation levels do not always lead to a higher demand for vaccines. The VH Determinants Matrix categorizes the factors influencing behavioral choices to take some vaccines, delay or reject them, or all vaccines into three categories: contextual, individual and group, and vaccination-specific issues.…”
Section: Therapeutic Advances In Vaccines and Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 In elaborating on the context, the WG asserted that reluctance was a behavioral phenomenon that was vaccine-specific and context-specific and is measured in the light of the available immunization services against an expectation of meeting a specific vaccine coverage goal. 7 Research conducted by Marti et al 8 indicated that while high hesitancy levels lead to lower demand for vaccines, low hesitation levels do not always lead to a higher demand for vaccines. The VH Determinants Matrix categorizes the factors influencing behavioral choices to take some vaccines, delay or reject them, or all vaccines into three categories: contextual, individual and group, and vaccination-specific issues.…”
Section: Therapeutic Advances In Vaccines and Immunotherapymentioning
confidence: 99%
“…5,6 In elaborating on the context, the WG asserted that reluctance was a behavioral phenomenon that was vaccine-specific and context-specific and is measured in the light of the available immunization services against an expectation of meeting a specific vaccine coverage goal. 7 Research conducted by Marti et al . 8 indicated that while high hesitancy levels lead to lower demand for vaccines, low hesitation levels do not always lead to a higher demand for vaccines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, ARIMA model has been widely used to simulate and forecast the epidemic tendency of infectious diseases and has achieved satisfactory effects [ 26 , 44 ]. In this work, we established a multiplicative ARIMA model due to the seasonal variations and annual periodicity of HFMD in Shanxi.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 20 ] reported different ARIMA models for different countries to forecast coronavirus incidence, and their model was selected based on AIC criteria. Tan et al [ 21 ] developed the seasonal autoregressive moving average (SARIMA) model for the analysis of the trend of the third wave of COVID-19 in Malaysia.…”
Section: Introductionmentioning
confidence: 99%